The Influence of Group Counseling on the Learning Difficulties in Arabic Language among Students of STAI As-Sunnah Tanjung - Muslim, Muslim; Abdurrahman, Abdurrahman; Darmayanti, Nefi (Lembaga Penelitian dan Pengabdian Masyarakat Institut Agama Islam Al-Khairat Pamekasan, 2024)
This study evaluates the impact of group counseling on addressing learning difficulties in Arabic among students at STAI As-Sunnah Tanjung Morawa. With its complex morphology and syntax, Arabic poses significant challenges for learners, particularly within Islamic education contexts. The research employs a pretest-posttest control group design to assess whether group counseling can improve students' proficiency in Arabic. Data collected through pretests, post-tests, and qualitative observations reveal that group counseling substantially improves students' Arabic skills. The average percentage of correct answers increased from 68.89% in the pretest to 97.22% in the post-test. These results suggest that group counseling is an effective intervention for overcoming difficulties in learning Arabic and enhancing language proficiency. The study highlights the importance of incorporating group counseling into educational practices to support students in mastering Arabic and achieving better learning outcomes.